Membrane-Protecting Effects of Perfluorane on Red Blood Cells in Acute Blood Loss (an experimental study) - V. V. Moroz; A. K. Kirsanova; I. S. Novoderzhkina; V. V. Aleksandrin; G. A. Nazarova (Общая реаниматология)
Objective: to evaluate the membrane-protecting effect of perfluorane (PF) on red blood cells during hypotension and at the early stages of the postreinfusion period, by applying its various administration regimens. Materials and methods. Experiments were carried out on 27 outbred male rats weighing 350 g. The model of the investigation was one-hour hypovolemic hypotension, followed by exsanguinated blood reinfusion. Changes in the ratio of different forms of red blood cells were studied in the blood smears. The cells were calculated under an Olympus BX-500 microscope, magnification 1000x. Three series of experiments were run, each included experimental and control groups. In the experimental groups, PF was administered in a dose of 3 ml/kg an hour before blood loss and 10 min and an hour after blood reinfusion. In the control groups, Ringer’s solution was given in the same volumes and in the same periods as in the experimental ones. Results. The positive effect of PF on the morphological parameters of red blood cells was observed in all the groups of experiments, but it differed in its magnitude depending on the time of PF administration. Preadministration of PF an hour prior to blood loss protected the erythrocyte membrane from hypoxic exposure during hypotension and increased the count of stages I—II planocytes and stomatocytes after blood reinfusion as compared to the controls. The similar results were also obtained with PF administration 10 min after blood reinfusion. In addition to the above effects, PF administration an hour following blood reinfusion promoted a reduction in the number of Stages III-IV stomatocytes. Conclusion. Thus, the most pronounced membrane-protecting effect of PF on red blood cells was obtained with its administration an hour after blood reinfusion. A slight weakening in the effect of PF during its preadministration or just after blood reinfu-sion seems to be associated with the PF-induced reduction in blood circulatory centralization that is known to be of considerable importance in compensation processes both during blood loss and at the early stages of the postresuscitation period. Key words: perfluorane, blood loss, red blood cell membrane.